Advancing the Sociology of Empathy: A Proposal. Issue 3 (19th May 2017) - Ruiz‐Junco, Natalia
Abstract : Empathy is an increasingly popular term in the public sphere and in academia. Although the common belief is that empathy is a "psychological" topic, sociologists have made important contributions to this conversation. The goal of this article is to provide a theoretical effort in advancing the sociology of empathy. In the first part of the paper, I review classical and contemporary statements on empathy. I identify Charles H. Cooley as an important precursor of the sociology of empathy, and discuss how contemporary interactionists have further developed this notion. Based on these previous insights, I next propose a preliminary framework for the study of the social construction of empathy. This framework is presented in two steps. First, I introduce a vocabulary based on interpretivist concepts: empathy frames, empathy rules, and empathy performances. Next, I coin the idea of empathy paths. I theorize three ideal‐typical empathy paths: self‐transcendent, therapeutic, and instrumental. Throughout this presentation, I use empirical cases to illustrate the applicability of this framework. In the conclusion, I show how sociologists can inform public understandings of the meaning of empathy.